Repeatibility and Reproducibility (RR) of Bioelectric Impedance Vectors in Brazilian Children with Normal Body Mass - Mangia, Cristina Malzoni Ferreira; Carneluti, Alexandre; Kopelman, Benjamin Israel; Carvalho, Werther Brunow de; Andrade, Maria Cristina (European Journal of Applied Sciences, 2023)
Background: Bioelectrical analysis measures two bioelectrical vectors: resistance (R) and reactance (Xc). Resistance is the pure opposition of a biological conductor to the flow of an alternating current through the intra and extra-cellular ionic solution and it is inversely related to the dynamics of body fluids and body composition. Objective: The purpose of this study was to determine the reference values of the indexes bioelectrical impedance (BI) for children of normal body mass index in southeastern Brazil of middle-income country. Methods: Two hundred eighty-one children with normal body mass index were included in the study (135 female and 146 male), aged 4 to 129 months, selected from federal public urban school in São Paulo, São Paulo, Brazil, where bioelectrical impedance values resistance (R) and reactance (Xc) values were measured in order to establish reference values of these parameters. Results: The anthropometric variables, body mass index, z-scores and bioelectrical impedance parameters were evaluated. For both genders, the mean and standard deviation of anthropometric variables were age (months): 73.42 + 34.65; weight (kg): 23.5 + 9.46; height (m): 1.16+0.22; BMI (kg/m2): 16.65+1,75; Xc (ohms): 63.92+9.6; R (ohms): 749+75.26. For analysis, the children were stratified into three groups for each gender, being divided by ages: 4 to 23 months; 24 to 71 months and 72 to 129 months. Linear regression analysis showed R had a significant progressive decrease with age (p=0.0003) while Xc had a progressive increase (p=0.0065) with age increase. We analyzed by multiple regression the associations between R and Xc with anthropometric variables by age group to establish the reference values, confidence intervals and the tolerance limits for a new individual observation. Test-Retest Repeatability between three repeat and consecutive measurements was considered excellent. Intraclass correlation coefficient and Bland -Altman reproducibility was for reactance 0.755, Resistance 0.98 and phase angle was 0.93. Conclusion: The BI reference values were established, in a field where there is a relative lack of publications, and we collected relevant information about resistance and reactance in a population of middle income setting that could be used in epidemiologic studies and could be used reference value in children with altered body composition.